Experiencia de Aprendizaje-Servicio online en una Escuela de Nutrición y Dietética de Santiago, Chile - Rodríguez Palleres, Ximena; Pino Astorga, Carolina; Neira Peña, Tanya; Cancino Bascuñán, Valentina (Universidad de Costa Rica, 2023)
The Service-Learning methodology enables students to apply theoretical knowledge in a real context, through the satisfaction of a need indicated by the community, where teachers guide the learning of the students. However, given the quarantine restrictions resulting from the COVID-19 pandemic, the Service-Learning activities of a School of Nutrition and Dietetics in Santiago, Chile were implemented remotely. The main objective of this study was to determine the perception of the Learning and Service experience in distance modality from the perspective of students and beneficiaries of a Chilean University during the 2020 academic year. This is quantitative research with a descriptive, cross-sectional, non-probabilistic convenience design. The sample consisted of 56 students and 28 beneficiaries from Santiago de Chile. To describe the perception of the experience, a survey developed and validated for this study was applied. Our results indicate that more than 50% of students and beneficiaries positively valued the activities in distance mode. The beneficiaries rated the experience with a higher grade than the students (Mbeneficiaries= 4.64 against Mstudents= 4.50; p = .321). In conclusion, the Service-Learning methodology in distance modality was well valued by the participants, being an implementation option.